2014
DOI: 10.3892/ol.2014.2720
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular location and photodynamic therapeutic effect of chlorin e6 in the human tongue squamous cell cancer Tca8113 cell line

Abstract: The present study aimed to investigate the distribution and photodynamic therapeutic effect of chlorin e6 (Ce6) in the human tongue squamous cell carcinoma Tca8113 cell line in vitro. The distribution of Ce6 in the Tca8113 cells was observed in situ combined with mitochondrial and lysosomal fluorescent probes. Next, 630-nm semiconductor laser irradiation was performed. The MTS colorimetric method was used to determine cell survival. Annexin V fluorescein isothiocyanate/propidium iodide (PI) double staining was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…The light dose of 3 J/cm 2 was selected based on the previous research on chlorin PDT. Chung et al and Luo et al suggested the range of light dose (1–5 J/cm 2 ) in both HCT116 human colon cancer cells and Tca8113 human tongue squamous cancer cells. In our preliminary study, we tested different light doses of 1 J/cm 2 , 3 J/cm 2 and 5 J/cm 2 , and only 3 J/cm 2 light dose resulted in a gradual increase in cellular toxicity as a function Ce6 concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The light dose of 3 J/cm 2 was selected based on the previous research on chlorin PDT. Chung et al and Luo et al suggested the range of light dose (1–5 J/cm 2 ) in both HCT116 human colon cancer cells and Tca8113 human tongue squamous cancer cells. In our preliminary study, we tested different light doses of 1 J/cm 2 , 3 J/cm 2 and 5 J/cm 2 , and only 3 J/cm 2 light dose resulted in a gradual increase in cellular toxicity as a function Ce6 concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Using Ce6-incubated murine bladder cancer cells, ROS production was further validated against red laser irradiation, the current clinical standard (24), in two configurations: (i) cells directly exposed to the radio-frequency/laser source, and (ii) cells placed under thick (3 cm) porcine tissue, simulating light delivery to deep tissue regions ( Fig. 3 E and F).…”
Section: Significancementioning
confidence: 99%
“…The breakdown of the plasma membrane releases all the cellular content leading to a strong inflammation [62]. It is generally accepted that high-dose PDT, either by applying a high photosensitizer concentration and/or a highdose light tends to kill cells by necrosis [14,[63][64][65]. Necrosis is also associated with photosensitizers having tropism for the cell membrane, which, upon photoactivation, mediate the loss of membrane integrity and ATP depletion.…”
Section: Accidental Necrosis (Non-regulated Cell Death)mentioning
confidence: 99%